Pengaruh Model Pembelajaran Word Square Terhadap Hasil Belajar IPA Pokok Bahasan Benda dan Perubahan Benda Pada Siswa Kelas V SD Negeri I Palir Kecamatan Tengah Tani Kabupaten Cirebon - Neli; Fanni Zulaiha; Yati; Adiman (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2020)
Science is one of the compulsory subjects in elementary school that must be achieved optimally. The results of learning science subject matter and object changes in grade V SD Negeri 1 Palir, Tengah Tani District, Cirebon Regency are still under the KKM. One creative learning model that can be used is the word square learning model. This study aims to determine the effect of the word square learning model on science learning outcomes. The research method used is the experimental method. The sampling technique in this study using saturated sampling. The population of class V students was 56 students. The research sample consisted of 28 people, who were grouped into experimental classes, the control group consisted of 28 students. Based on the hypothesis of the results of the T test, it is found that tcount> ttable or T11.083<T 2.005, which means H1 is accepted. This means there are differences in science learning outcomes between the word square learning model and the lecture method. In addition, in the N-gain test based on the calculated N-gain control value = 0.074 0.566, it means that there is a difference in science learning outcomes between using the word square model and using the lecture method. Which means that the Word Square model has an effect on science learning outcomes. Student responses to the word square model on the learning outcomes of science learning materials and object changes in class V are very strong.